Um exercício de literatura comparada. Lendo Remember Ruben de Mongo Beti e a Vida Verdadeira de Domingos Xavier de Luandino Vieira - Venâncio, José Carlos (Africana Studia, 2020)
Remember Ruben of Mongo Beti (Cameroon) e A vida verdadeira de Domingos Xavier (The true life of Domingos Xavier) of LuandinoVieira (Angola) are two foundationist novels of the socalled nationalist paradigm. This comparative analysis inends, on one hand, to discover the social and politica! contexts, which its aesthetic values are based on and, on the other hand, to isolate the aesthetic aspects responsible for its actuality.